From news images to action: the mobilizing effect of emotional protest images in news coverage - Stephanie Geise; Diana Panke; Axel Heck (Frontiers in Political Science)
The political power of images has probably never been stronger than in today's “information age” in which mobile devices allow instant access to news coverage of local, national, and global events, which are generally visualized in some way. Thus, this paper investigates whether political news images mobilize people to engage in political protest by appealing to their emotions. A pre-post-design integrating eye tracking with 143 participants examines how the observation of protest images in news coverage induces emotions and affects participatory intents. This reveals that a longer image observation activates both positive and negative discrete emotions (i.e., fascination, interest, sadness, anger, disgust, shame, guilt, and being touched) which increase the image recipients' willingness to participate politically. Additionally, for people with a high level of political interest, longer exposure to an emotion-inducing news image increases their willingness to participate in political activism, while a low level of political interest produces a negative effect.